(untitled) (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2021)
Geriatrics is the group of people who experience many complex health problems. Poly pharmacy increases the incidence of ADRs, drug interactions, non-compliance which leads to increase in hospital admissions and thus increase health expenditure. Therefore, studies on the assessment of appropriateness of prescribing pattern and drug therapy in elderly particularly in our country are needed to better support decision making process. The study can also give insight into trends in using drugs in elderly and in treating their co-morbid conditions. The objectives of the study are to analyse the appropriateness of prescribing pattern in geriatric patients with multiple co-morbid conditions in the selected study population as per inclusion criteria. A prospective observational study was conducted. The data was collected during regular ward rounds and was analyzed. The appropriateness of the prescription was analyzed by using the Beers criteria. WHO core prescribing indicators was used to analyze the prescribing pattern. A total of 120 patients were included in the study. The analysis of appropriateness of prescribing pattern as per Beers Criteria shows that 45 (37.5%) were found to be appropriate and 75 (62.5%) were found to be inappropriate prescriptions. A total number of 153 medications prescribed were found to be potentially inappropriate for geriatric use as per Beers criteria. Analyzing prescriptions as per WHO core prescribing indicators were done, the results reveals that there was an average of 12.92 drugs per prescription, 102 (6.58%) drugs were prescribed by generic name, percentage of encounters with antibiotics was 77.5% and percentage of encounters with injections prescribed were 98.3%. From these results, the prescriptions were found to be irrational according to WHO core prescribing indicators. A key role can be played by the clinical pharmacist to manage drug therapy in collaboration with prescribers for preventing drug related problems resulting from inappropriate medication use in geriatric patients. The study concluded that close monitoring of prescriptions can help to avoid majority of drug related problems and improving the quality of care among the geriatric patients.